MHD heat transfer and entropy generation in inclined trapezoidal cavity filled with nanofluid Numerical investigation and sensitivity analysis - Shirvan, Kamel Milani; Mirzakhanlari, Soroush; Öztop, Hakan Fehmi; Mamourian, Mojtaba; Al-Salem, Khaled (Emerald Group Publishing Ltd, 2017)
Purpose - The main purpose of this paper is to define 2D numerical study and a sensitivity analysis of natural convection heat transfer and entropy generation of Al2O3-water nanofluid in a trapezoidal cavity, with considering of the presence of a constant axial magnetic field. Design/methodology/approach - The effects of the three effective parameters, the Rayleigh number, Hartmann number (Ha) and also inclination angle on the heat transfer performance and entropy generation, are investigated using a finite volume approach. The sensitivity analysis of the effective parameters is done utilizing the response surfacemethodology. Findings - The results obtained showed that the mean Nusselt number and total entropy generation increase with the Rayleigh number. Also, increasing the inclination angle reduces the mean Nusselt number (regardless of the magnetic field). In addition, it is found that the mean Nusselt number increases until Ha = 10 and then decreases by increasing of Ha number, regardless of the inclination angle. The sensitivity of the mean Nusselt number to the Ha number and inclination angle a is negative. It is concluded that to maximize the mean Nusselt number and minimize the entropy generation, simultaneously, the Ha and inclination angle must be 50 degrees and 0 degrees, respectively. Originality/value - There is no published research in the literature about sensitivity analysis of magneto-hydrodynamic heat transfer and entropy generation in inclined trapezoidal cavity filled with nanofluid.
Keywords: Natural convection; Inclination angle; Response surface methodology; MHD; Entropy generation; Sensitivity analysis